Morphometry in Oral Leukoplakia with Epithelial Dysplasia - Yisel Alonso Vila; Galia Ivis Pérez Rumbaut; Pedro Augusto Díaz Rojas; Laura Naranjo Hernández; Yamilka Mesa González; Marlén Llanes Torres (Revista Finlay, 2025)
Foundation: oral leukoplakia is the most common potentially malignant lesion of the oral mucous membranes and carries a proven risk of developing oral cancer. Objective: to characterize oral leukoplakia according to the degree of epithelial dysplasia using morphometric and stereological parameters. Method: a case series study was conducted to determine morphometric indicators of leukoplakia lesions of the oral mucosa in biopsies from patients seen in the Pathology and Maxillofacial Departments of Dr. Gustavo Aldereguía Lima General University Hospital in Cienfuegos. The sample was obtained by purposive sampling and consisted of 30 histological slides. The study variable was the morphometric characterization of leukoplakia of the oral mucosa with dysplasia. Descriptive and inferential statistics were applied. Results: there was statistical significance in the nuclear shape factor; as the degree of dysplasia increased, there was a greater degree of nuclear pleomorphism. In nuclear volume, descriptive statistics showed a downward curve from mild to severe dysplasia. Conclusions: as the degree of dysplasia increased, there was a greater degree of nuclear pleomorphism. Descriptive statistics showed a downward curve from mild to severe dysplasia.